The Problems of Rapid Urbanisation in Port Harcourt (Global Journal of Human-Social Science, 2020)
This work examines the problems of Rapid Urbanisation in Port Harcourt as a cosmopolitan city which has attracted migrants from all parts of the world, and these problems have attracted the attention of both the State and Federal Governments because of the realization that if the present pace of urbanization is not checked, the benefits of urbanization will be counterproductive. Therefore, this study looked at the extent to which the housing stock is replenished, the pace of urbanization and how it matches the rate of employment generation, how well was the provision of infrastructures such as roads, social services, etc. whether they were adequate to meet the needs of the bourgeoning populace, and whether the mono-city status of Port Harcourt accounts for the congestion and criminal activities experienced in Port Harcourt. Primary and secondary data were collected and analysed. Our findings revealed that the mono-city status of Port Harcourt contributed greatly to the congestion of the city and accounts for the criminal activities experienced to a large extent.